Reframing academic leadership - Bolman, Lee G.; Gallos, Joan V. (San Francisco, CA : Jossey-Bass, 2011)
"The powerful tool of "reframing" can be applied to the challenges of higher education leadership. The book uses the authors Lee Bolman and Joan Gallos's four frames (Structural, Human Resource, Political, Symbolic) developed by Bolman and Deal to illustrate different views of academic leadership. The Structural Frame: The Human Resource Frame: The Political Frame: and The Symbolic Frame. This will prove to be an invaluable recourse for deans directors, vice presidents, provosts, department chairs who are interested in reframing their institutions"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Educational leadership; Higher education